Increasingly frequent compound climate events worsen economic disparities in China's urban agglomerations - Chao He; Liling Chu; Yiqi Zhou; Yanwen Wang; Yilin Li; Qixin Hu; Song Hong; Chunping Miao (Urban Climate, 2026)

Spatiotemporal evolution and attribution of urban exposure to compound precipitation and wind speed extremes in China since 1980 - Liling Chu; Chao He; Yang Jiang (Anthropocene, 2025)

Climate change and human activities drive the warm-season rooftop solar photovoltaic potential in the Chinese Chengdu-Chongqing urban agglomeration - Yilin Li; Lijun Liu; Tianyu Zhang; Youjia Liang; Zhenghong Chen; Liling Chu; Chao He (Sustainable Cities and Society, 2025)

Clinical Diagnosis and Differential Diagnosis Between CSF1R- and AARS2-Related Leukoencephalopathy - Chenhui Mao; Yuyue Qiu; Tianyi Wang; Yuhan Jiang; Shanshan Chu; Wei Jin; Liling Dong; Jing Gao (Journal of Molecular Neuroscience, 2025)

Unveiling the dynamics of dry-and-humid, day-and-night, and compound heat waves across 209 Cities in China during 1974–2021 - Lijun Liu; Liling Chu; Youjia Liang; Jiangang Li; Miao Yu; Chao He (Urban Climate, 2024)

Invigorating active sites for amorphous/crystalline heterophased co-based oxyhydroxide/tungstate toward enhanced electrocatalytic oxygen evolution: Trimetallic codoping-achieved synergistic regulation - Jiejie Feng; Jianting Liu; Changshun Chu; Liling Wei; Huayi Li; Jianquan Shen (Chemical Engineering Journal, 2024)

Association Between Wnt Target Genes and Cortical Volumes in Alzheimer’s Disease - Liling Dong; Bo Hou; Caiyan Liu; Chenhui Mao; Xinying Huang; Li Shang; Shanshan Chu; Bin Peng; Liying Cui; Feng Feng; Jing Gao (Journal of Molecular Neuroscience, 2023)
The disproportionate cortical atrophy is an established biomarker for the pathophysiological process of Alzheimer’s disease (AD). However, the genetic basis underlying the cortical atrophy remains poorly defined. Herein, we aim to illustrate the effect of the Wnt target genes on the cortical volumes of AD patients. 82 sporadic AD patients were recruited. All the subjects had history survey, blood biochemical examination, cognitive assessment, MRI morphometry and whole exome sequencing. This report focused on 84 common variants (minor allele frequency > 0.01) of 32 Wnt target genes, including the APC , DAAM1 , DACT1 , DISC1 , LATS2 , TLR2 , WDR61 , and the AXIN , DVL , FZD , LRP , TCF/LEF , WNT family genes. The Wnt target genes showed asymmetric effects on the cortical volumes of AD patients. The right temporal/parietal/occipital cortices were more affected than left temporal/parietal/occipital cortices. Nevertheless, the reverse applied to the frontal cortex. The DACT1 affected the cortical thickness most, followed by the TCF3 and APC . The DACT1 rs698025-GG genotype displayed greater right temporal pole and left medial orbito-frontal gyrus than rs698025-GA genotype (2.4 ± 0.4 vs. 2.0 ± 0.6, P = 0.005; 5.2 ± 0.6 vs. 5.0 ± 0.6, P = 0.001). The brain region most influenced by the Wnt target genes was the right calcarine cortex. In conclusion, the common variants of the Wnt target genes exert asymmetric effects on the cortical volumes of AD patients. The Wnt signaling pathway may play a role in the cortical atrophy of AD patients.

Evaluating the contribution of climate change and urbanization to the reversal in maximum surface wind speed decline: Case study in the Yangtze River Economic Belt, China - Lijun Liu; Youjia Liang; Chao He; Bin Li; Liling Chu; Jiangang Li (Urban Climate, 2023)

Phenotype Heterogeneity and Genotype Correlation of MAPT Mutations in a Chinese PUMCH Cohort - Chenhui Mao; Liling Dong; Jie Li; Xinying Huang; Dan Lei; Jie Wang; Shanshan Chu; Caiyan Liu; Bin Peng; Liying Cui; Jing Gao (Journal of Molecular Neuroscience, 2021)